The other Latin@ : writing against a singular identity - Falconer, Blas; López, Lorraine, 1956- (University of Arizona Press, 2011)
""The stereotype spells death to the imagination by shrinking all possibilities to one. Generalizations encourage us to stop considering what can be."--The Introduction The sheer number of different ethnic groups and cultures in the United States makes it tempting to classify them according to broad stereotypes, ignoring their unique and changing identities. Because of their growing diversity within the United States, Latinas and Latinos face this problem in their everyday lives. With cultural roots in Mexico, Puerto Rico, Cuba, the Dominican Republic, or a variety of other locales, Hispanic-origin people in the United States are too often consigned to a single category. With this book Blas Falconer and Lorraine M. López set out to change this. The other Latino is a diverse collection of essays written by some of the best emerging and established contemporary writers of Latin origin to help answer the question: How can we treat U.S. Latina and Latino literature as a definable whole while acknowledging the many shifting identities within their cultures? By telling their own stories, these authors illuminate the richness of their cultural backgrounds while adding a unique perspective to Latina and Latino literature. This book sheds light on the dangers of abandoning identity by accepting cultural stereotypes and ignoring diversity within diversity. These contributors caution against judging literature based on the race of the author and lament the use of the term Hispanic to erase individuality. Honestly addressing difficult issues, this book will greatly contribute to a better understanding of Latina and Latino literature and identity"-- Provided by publisher.
Keywords: American literature -- Hispanic American authors -- History and criticism.; Identity (Philosophical concept) in literature.; Stereotypes (Social psychology) in literature.; Characters and characteristics in literature.; Hispanic Americans -- Intellectual life.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Identité dans la littérature.; Stéréotypes dans la littérature.; Américains d'origine latino-américaine -- Vie intellectuelle.; LITERARY COLLECTIONS -- Essays.; LITERARY COLLECTIONS -- General.; American literature -- Hispanic American authors; Characters and characteristics in literature; Hispanic Americans -- Intellectual life; Identity (Philosophical concept) in literature; Stereotypes (Social psychology) in literature; Literatur; Hispanos; Identität; Stereotyp; USA; Criticism, interpretation, etc.; Electronic books.